Continuous microwave pasteurization of a vegetable smoothie improves its physical quality and hinders detrimental enzyme activity - Arjmandi, Mitra (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2017)
© The Author(s) 2016.